Kualitas Servis Pendek Forehand Dan Smash Pada Bulutangkis Di Club PB Ramba Jaya - Didik Purwanto; Arief Aditya Rifandy; Rahmah Rahmah; Delvi Liloi Kristanti Liloi; Kungku Kungku; Hendrik Mentara; Tri Murtono (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
This study aims to analyze how the basic techniques of short serve forehand and smash in badminton games at Club PB. Rama Jaya. The population in this study were Club PB athletes. Rama Jaya. The sample in this study amounted to 20 athletes. The sampling technique in this study used Non-probability Sampling with the Quota Sampling technique. The instrument used in data collection is the short serve test forehand and smash in badminton games. Based on the results of research on the level of basic technical skills in badminton games at Club PB. Ramba Jaya researchers can conclude that there are 2 athletes who fall into the